"I am actually doing alright" : a grounded theory exploration of how women's online social support use affects maternal identity construction and wellbeing : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University, Palmerston North, New Zealand - Swale, Lisa Elizabeth (Massey University, 2019)
In the maternal transition constructing a mothering identity is challenging as maternal identities are shaped by socially constructed ideologies of “good” motherhood. These idealised constructions are conveyed through women’s social support – in both online and offline spaces – and ultimately influence wellbeing. Online support is growing in prevalence and women are increasingly going online for maternal support. This study explores how online social support use, particularly the Social Networking Site Facebook, influenced New Zealand women’s maternal identity construction and its potential effects on wellbeing. This grounded theory study analysed in-depth semi-structured interviews (n=14) to capture the experiences of New Zealand women who had recently undergone the transition to motherhood. The constant comparison approach was used for analysis. The findings provide insights into these new mothers’ experiences of using online social support in their maternal identity construction. The produced framework enables understanding of how women used online social support to negotiate their maternal identity construction. Women manage this identity by using online social media to: (1) create a “base” of support in gaining information; (2) create a “village” of support for intimate connections; (3) compare their mothering experiences; and (4) mentor other new mothers in re/constructing their maternal identity. The proposed framework explains how online social support access, particularly Facebook, gave women choice in support and enabled opportunities to create mothering communities. The analysis shows how “villages” were used in the negotiation of maternal identity and re/construction of what it means to be a “good” mother within women’s individual contexts. Thus, women learnt to manage their identity construction online in ways that enhanced perceived connectedness, support, confidence and overall wellbeing. Insights into new mothers’ use of online social support to manage the re/construction of maternal identity and its ability to shape maternal wellbeing have implications for support provision by healthcare professionals.
Keywords: Motherhood; New Zealand; Psychological aspects; Mothers; Psychology; Identity (Psychology); Social media; Attitudes; maternal transition; maternal identity; construction; wellbeing; online social support; Facebook; 520599 Social and personality psychology not elsewhere classified